Development of A Real-time IoT Data Logger for API Index Monitoring - Sabarudin, Nur Azizah; Sadun, Amirul Syafiq; Rosli, Mohd Arif; Chong, Kar Kar (Progress in Engineering Application and Technology, 2022)
PM2.5 is one of the criteria of the Air Pollution Index (API) which is used in Malaysia to measure ambient air quality. It is critical to keep an eye on PM2.5 levels for air quality monitoring, especially in densely populated area with continuous construction and development. However, the PM2.5 samplers used in research and monitoring are in manual mode, where data is stored into the equipment data logger and manually extracted from the data logger to a personal computer through cable. This makes it challenging for the person in charge of monitoring and reporting real-time air pollutant data when the access to the E-Sampler site is limited, such as in the event of pandemic, haze and toxic pollution. However, the issue can be solved with utilization of Internet of Things (IoT) and its components into the monitoring system. This project therefore proposes the construction of IoT Data logger capable of uploading real-time data from the E-Sampler to cloud and develop a mobile phone application that connect to the same cloud to enable the wireless data extraction from the deployed measurement tool as well displaying the data in graphical form for monitoring purpose through mobile phone.